2019
DOI: 10.3390/jrfm12010043
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Global Oil Price on Exchange Rate, Trade Balance, and Reserves in Nigeria: A Frequency Domain Causality Approach

Abstract: This study investigated the relative Granger causal effects of oil price on exchange rate, trade balance, and foreign reserve in Nigeria. We used seasonally adjusted quarterly data from 1986Q4 to 2018Q1 to remove predictable changes in the series. Given the non-stationarity of our variables, we found cointegration to exist only between oil price and foreign reserve. The presence of cointegration implied the existence of long run relationship between the variables. The Granger causality result showed that oil p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 33 publications
1
11
0
1
Order By: Relevance
“…Similarly, it was discovered that oil revenue has positive and non-statistical significant influence on foreign reserves in Nigeria. This result is similar to Bankole and Shuaibu (2013) and Olayungbo (2019), where their study also discovered a relationship between oil revenue and foreign reserves but the relationship is statistically insignificant. Lastly, total debt has a positive and statistically non-significant influence on foreign reserves.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Similarly, it was discovered that oil revenue has positive and non-statistical significant influence on foreign reserves in Nigeria. This result is similar to Bankole and Shuaibu (2013) and Olayungbo (2019), where their study also discovered a relationship between oil revenue and foreign reserves but the relationship is statistically insignificant. Lastly, total debt has a positive and statistically non-significant influence on foreign reserves.…”
Section: Discussionsupporting
confidence: 88%
“…The outcome of this results is similar to Asagunla and Agbede (2018) who discovered oil revenue to be statistical insignificant in relation to economic growth. Similarly, Olayungbo (2019) in his study found out that, there is a relationship between oil price revenue and foreign reserves but the relationship is statistically insignificant. Also, Bankole and Shuaibu (2013) discovered only a marginal or insignificant impact of oil revenue on foreign reserves.…”
Section: Regression Analysismentioning
confidence: 88%
See 1 more Smart Citation
“…Many studies on the nexus between oil price and exchange rate in Nigeria employed traditional methods of analysis, such as OLS, Co-integration, Vector autoregressive and autoregressive distributed lag method (Ademola and David 2011 ; Umoru et al 2018 ; Bankole and Shuaibu 2013 ; Olanipekun 2016 ; Olayungbo 2019 ). However, the relationship might not necessarily be linear.…”
Section: Introductionmentioning
confidence: 99%
“…Örneğin; Gronwald (2008) Almanya için, Yanfeng (2019) Japonya için, Albulescu vd. (2017) Romanya için ve Olayungbo (2019), Nijerya için petrol fiyatları ile makroekonomik değişkenler arasındaki ilişki frekans alanında nedensellik testi ile araştırmıştır.…”
Section: Literatürunclassified